O efeito da toxina botul??nica tipo A sobre a espasticidade e funcionalidade da crian??a com paralisia cerebral esp??stica - Souza, Maria Eliege de (2015)
The cerebral palsy (CP) is characterized by a group of non progressive disorders of the brain???s development and posture caused by a malformation or brain injury. As treatment , there are therapeutic approaches aimed at normalizing muscle tone and prevent change in the relation between bone growth and muscle, that can lead to poor posture and structured deformities. The aim this study was to investigate the effects of botulinum toxin type A (TB-A) for spasticity and functionality in spastic CP childrem. This was a prospective, controlled, randomized, consisting of 24 children (aged 5 to 12 years) with spastic CP, being divided into two groups: experimental group (EG) consisting of 12 patients (mean age 7.83 ?? 2, 07 years) treated with TB-A toxin and physiotherapy and control group (CG) with 12 patients (mean age 8.50 ?? 2.17 years) treated only with physical therapy. All participants were assessed through motor and functional scales (GMFCS, GMFM-88, Ashworth, Berg Balance Scale, Time up and go -TUG and Inventory Assessment Pediatric Disorders - ASK) at three different times: before treatment, 30 days and 3 months after the treatment proposed. By analysis of variance (ANOVA) for repeated measures it was observed significant differences (p < 0.001) between groups (groups vs treatment) to the data obtained in the GMFCS, GMFM-88, BERG, TUG, Ashworth and ASK, being observed functional improvement only for the GE group. In this study it was concluded that the use of TB-A provides a significant improvement on spasticity and child functionality with spastic CP, over a period of up to 3 months after application.